2012
DOI: 10.1212/wnl.0b013e31826958bf
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular therapy in children with acute ischemic stroke

Abstract: This review provides a summary of the currently available data pertaining to the interventional management of acute ischemic stroke in children. The literature is scarce and is lacking muchneeded prospective trials. No study in the literature on the well-established systemic or local thrombolysis trials has included children. Mechanical thrombectomy trials using clot retriever devices have also excluded patients younger than 18 years. The current review is limited to case series of interventional acute ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 43 publications
0
58
0
2
Order By: Relevance
“…pediatric patients were excluded from these studies. When used in children, Ellis et al 10 found a recanalization (partial or complete) rate of 74% with a relatively high complication rate of 29%. The cause of the high complication rate was not discussed, but one can speculate that smaller pediatric vessels likely contribute.…”
Section: Reperfusion Strategies In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…pediatric patients were excluded from these studies. When used in children, Ellis et al 10 found a recanalization (partial or complete) rate of 74% with a relatively high complication rate of 29%. The cause of the high complication rate was not discussed, but one can speculate that smaller pediatric vessels likely contribute.…”
Section: Reperfusion Strategies In Childrenmentioning
confidence: 99%
“…most patients in this review received intra-arterial tpA alone, whereas a minority received mechanical thrombectomy. 10 Although mechanical thrombectomy is an option for children with significant neurological deficits and arterial occlusion, it remains experimental and should only be undertaken when families are aware of the risks.…”
Section: Reperfusion Strategies In Childrenmentioning
confidence: 99%
“…‘Ad hoc' catheter revascularization and other stroke interventions are increasingly performed immediately following the diagnostic angiographic component of the procedure. The scope of stroke interventional diagnostics in specialty populations such as pediatrics and pregnancy have already been established, but continue to grow and evolve with regard to therapeutic measures in stroke intervention [37,38]. …”
Section: Introductionmentioning
confidence: 99%
“…Gecikmiş tedavilerde (2-18 saat arası, ortalama 14 saat) bile %38 kısmi, %35' inde ise tam rekanalizasyon sağlanabildiği gösterilmiştir. Olguların %23,5' inde işlem sonrası komplikasyon olarak beyin içi kanama gelişmişse de bunların sadece %2.9'unun (bir olgu) semptomatik olduğu bildirilmektedir (13). Ülkemizde pediatrik endovasküler trombektomi deneyimi henüz erişkinlerde yapılan uygulamalarla kıyaslanabilecek ölçüde değildir.…”
Section: Discussionunclassified